Building Alignment and Sparking Momentum with Tangible Future Scenarios. (1st August 2018) - Lawrence, Jill; Clark, Brendon
Abstract : Tangible Future Scenarios use props, improvisation, and a cooperative approach to invite discussion and drive further iterations with stakeholders. This storytelling approach aims to align people and ideas more quickly.